Dynamic characteristics of a two-phase mechanically pumped cooling loop for avionics - Shaohuan Qi; Zhaohao Xu; Jiale Wang; Yu Xu (Case Studies in Thermal Engineering)
Given the varying flight conditions and mission requirements that affect aircraft cold sources and heat loads, it is crucial to investigate the dynamic behavior of a two-phase mechanically pumped cooling loop (MPCL) for avionics. Here, an experimental MPCL system charged with R134a was established, and its performance was evaluated under cold source temperatures of 16–46 °C and heat fluxes of 50–150 kW/m2. When the cold source temperature varies, the heating wall temperature and pressure drop are 33.7–60.0 °C and 78.0−119.6 kPa for unadjustable pump mode, and they are 34.1–60.0 °C and 59.6−124.6 kPa for adjustable pump mode. When heat load starts, the heating wall temperature and pressure drop rapid rise, and then stabilize. For low temperature start-up, the heating wall temperature is lower, but the pressure drop is usually higher compared to high temperature start-up. When heat load jumps, heating wall temperature and pressure drop rise and then stabilize regardless of pump mode. The pump mode has a minor impact on the heating wall temperature, but the pressure drop is greater in adjustable mode than in unadjustable mode. The findings indicate the designed MPCL can always tend to be stable when the cold source or heat load change.